Analysis of metabolome changes in the HepG2 cells of apatinib treatment by using the NMR‐based metabolomics. Issue 11 (1st July 2019) - Gu, Jinping; Shu, Dan; Su, Feng; Xie, Yuanyuan; Liang, Xianrui
Abstract: Neovascularization is required for the growth of tumors, vascular endothelial growth factor (VEGF) and related signal pathways are important in tumor angiogenesis. Apatinib is a highly selective and potent antiangiogenesis drug targeting the receptor of VEGFR2, blocking downstream signal transduction and inhibiting angiogenesis of tumor tissue. Apatinib has a wide range of antitumor activities in vitro and in vivo, but its effect on metabolic changes has not deeply research at present. Nowadays, our research first systematically studied the metabolic changes affected by apatinib in the HepG2 cells at the half‐maximal inhibitory concentration value. We used the metabolomics by using 1 H nuclear magnetic resonance ( 1 H‐NMR) to analyze the HepG2 cell culture media. Multivariable Statistics was applied to analyze the 1 H‐NMR spectra of the cell media, including principal component analysis, partial least squares discriminant analysis (PLS‐DA) and orthogonal PLS‐DA (OPLS‐DA). Compared with the uncultured and cultured media (negative/positive control), the metabolic phenotypes were changed in the apatinib treatment with a continuous effect over time. The metabolic pathway analysis is shown that the mainly disturbed metabolic pathways pyruvate metabolism, alanine, aspartate, and glutamate metabolism and amino acid metabolism associated with them in the apatinib treatment. The differential metabolites which were identified from the reconstructed OPLS‐DA loading plots also reflected in these disturbed metabolic pathways. Our works could allow us to well understand the therapeutic effect of apatinib, especially in metabolism. Abstract : We first systematically studied the metabolic changes affected by apatinib in the HepG2 cells at the half‐maximal inhibitory concentration value. The metabolic pathway analysis is shown that the mainly disturbed metabolic pathways pyruvate metabolism, alanine, aspartate, and glutamate metabolism and amino acid metabolism associated with them in the apatinib treatment. Our works could allow us to well understand the therapeutic effect of apatinib, especially in metabolism.